Does Non-farm Income Affect Food Security? Evidence from India - Rahman, Andaleeb; Mishra, Sumit (The Journal of development studies, 2020)
Livelihood diversification through greater non-farm activities has been considered as an important mechanism to propel growth, lower rural poverty and augment farm income across developing countries. Little, however, is known about its implications for nutritional outcomes such as dietary diversity. Using a nationally representative panel survey of rural households in India, and night-time light intensity as an instrumental variable (IV) for non-farm income, we show that engaging in non-agricultural livelihood has a positive effect on overall food expenditure, especially on non-cereal items, enabling greater dietary diversity. These findings have crucial policy implications for nutrition transition in India where agricultural incomes have been stagnant during the last decade. Our findings further contribute to the existing knowledge of agriculture-nutrition pathways.